Romantic Children: On the Brink of Life and Death - Zwolińska, Barbara (Porównania, 2023)
The article is an attempt at a cross-sectional view of the principles of constructing a child hero in the literature of Polish Romanticism, with reference to characters from selected popular literature of that period. The breakthrough that took place in the way of presenting the child, its experiences and emotions, and the evaluation of childhood by the creators of Romanticism inspires us to seek answers to the questions about what values were noticed in children, what made them unique, how their relationships with adults were shaped (including with parents), with peers and siblings, which was the specificity of their sensitivity and differences in the way they perceive the world (the role of imagination and dreams) and confrontation with the experiences of existence, often traumatic, leading to suicide. The discovery of the child as an autonomous being resulted in a revolutionary approach of artists of Romanticism, making the immature beings, alongside the mad, the people and the poets, revelators of the romantic world view, including epistemology based on an extra-rational way of getting to know the world and explaining its complex mechanisms.